Seasonal variation of size-fractionated particulate matter in residential houses in urban area in Vietnam: relationship of indoor and outdoor particulate matter and mass size distribution - Vo Le-Ha T.; Yoneda Minoru; Nghiem Trung-Dung; Sekiguchi Kazuhiko; Fujitani Yuji; Shimada Yoko (E3S Web of Conferences, 2022)
The study aims to determine the concentration, size distribution and analyze the relationship of indoor and outdoor particles in urban area, in Vietnam. One thousand two hundred daily samples of PM0.1, PM0.1-0.5, PM0.5-1, PM1-2.5, PM2.5-10, PM>10 were taken simultaneously at four residential houses in summer and winter by nano sampler (Model 3182, Kinomax). The average concentrations of indoor PM0.1, PM0.5, PM1, PM2.5 and PM10 were in range of 5.3-8.9 μg/m3; 10.8-20.1μg/m3; 20.5-47.6 μg/m3; 33.7-105.9 μg/m3 and 44.7-135.0 μg/m3 among four houses, respectively. The concentrations of outdoor PM2.5, PM10 were considerately higher than those of indoor PM, whereas negligible differences on concentrations of PM0.1, PM0.5 and PM1 were observed. The significantly seasonal variation was observed for indoor PM1, PM2.5 and PM10, but not for PM0.1 and PM0.5. Majority of indoor fractions were origin from outdoor sources. Unimodal distributions of indoor particles determined the super-micron size (1 to 2.5 μm) with highest concentration and PM<0.5 and PM>10 with lowest concentration. Fine particles with interval sizes (PM0.5-1 and PM1-2.5) contributed to the predominance to coarse particles in both indoors and outdoors, suggesting serious threat on human health.